Periconceptional vitamin supplementation and neural tube defects; evidence from a case-control study in Western Australia and a review of recent publications. Issue 2 (April 1992) - Bower, C; Stanley, F J
Abstract : STUDY OBJECTIVE--The aim was to assess the association of neural tube defects with periconceptional vitamin supplementation. DESIGN--This was a matched, population based case-control study. SETTING--Western Australia, 1982-1984. PARTICIPANTS--Mothers of 77 cases (93% of those eligible) with isolated neural tube defects, mothers of 77 matched control infants with defects other than neural tube defects (control group I), and mothers of 154 liveborn, matched, control infants with no birth defects (control group II) participated in the study. MEASUREMENTS AND MAIN RESULTS--Information was collected by interview and self administered questionnaire. Crude and adjusted odds ratios (and their 95% confidence intervals) showed a small but non-significant protective effect of folate supplementation in comparisons with both control groups. The adjusted ratios for the three months before pregnancy were 0.69 (0.06, 8.53) with control group I, and 0.11 (0.01, 1.33) with control group II. In the first six weeks of pregnancy, the adjusted odds ratios were 0.70 (0.32, 1.52) with control group I and 0.74 (0.29, 1.88) with control group II. The odds ratios for vitamin supplementation of any kind were all very close to or greater than one, and all confidence intervals embraced unity. CONCLUSIONS--These data do not provide evidence of an association between periconceptional vitamin supplementation and neural tube defects, although a protective effect of folate supplementation cannot be excluded with confidence, due to the low power of the study. Of three other observational studies of vitamins and neural tube defects, two have shown an association. While further studies of this kind may be of value, evidence must now be sought from randomised controlled trials.